Decision Making Power of Homemakers in a Rural Muslim Community of West Bengal: An Empirical Study - Samsunnehar (ACCB Publishing, 2021)
Decision-making power is a vital key for assessing the empowerment of a person. Empowerment increases self-efficacy by which one can control one’s mode of life for survival in a better way. It is an established fact that women are the most disempowered section in our society and the rural Muslim women are relatively more oppressed than others as there is the predominance of social-cultural and economic inequality among this minority community. As a result, these women have very limited opportunities to participate in the decision-making process related to their family matters and societal affairs linked with their own lives. Considering this scenario, the present study attempts to examine and analyse the decision-making power of homemakers in rural Muslim communities at micro level, taking Santoshpur village of Murshidabad district, West Bengal, as a case study. The methodology designed for the present study integrates both quantitative and qualitative methods based on field surveys. For this, fifty respondents have been selected using stratified purposive random sampling technique, and data have been acquired through face-to-face interviews through a semi-structured questionnaire. Then, the Cumulative Empowerment Index (CEI) is constructed based on selected eight key indicators to measure respondents' decision-making ability and liberty. Multiple Correlations are also computed, indicating that education and economic dependencies are the most critical determinants influencing women's empowerment and decision-making processes. The study also reveals that the existing rigid cultural system is mainly responsible for the suppression of women’s identity as well as their thoughts. But there remains hope for the next-generation girl children as different schemes are being taken up by the Government of West Bengal to promote and popularise women’s education at different levels.